Idiozetes malgache, a new species of Idiozetidae (Acari: Oribatida) from Madagascar - Fernández, Néstor Alfredo (2010)
Idiozetes malgache n. sp., collected from Madagascar, is described and illustrated, based on adult specimens. This new species is distinguishable from the two other known species in the genus by the following set of characters: cerotegument thick; elongate-polygonal reticula on prodorsum and plicate smooth layer on notogaster; cuticle smooth; ro and le present; in absent; pteromorphs narrow with a pointed tip; discidium present; four pairs of sacculi; six pairs of gastronotic setae; five pairs of lyrifissures; epimeral setation (3-1-2-3); six pairs of genital setae; legs heterotridactylous, sockets incomplete on tibia I to IV and genu I and II; setal formula: I (0-4-3-4-17-3) (1-2-2); II (1-4-3-2-14-3) (1-1-2); III (1-2-1-3-13-3) (1-1-0); IV (0-2-2-3-13-3)(0-1-0). The genus is redefined. © 2010 Taylor & Francis.